Monetary Policy in Unified Currency Areas : The Cases of the Cama and Ecca During 1976-90 - Nascimento, Jean-Claude (IMF Working Papers; Working Paper ;, 1994)
The paper compares the performance of monetary policy in the Central African Monetary Area (CAMA) and the Eastern Caribbean Currency Area (ECCA) during 1976-90. Their institutional setup and mechanism for monetary control are examined to explain the opposite trends in the net external position of their banking system during this period. It concludes that monetary policy in the ECCA succeeded by relying on active interest rate management aimed at stemming capital outflows and adhering to stringent rules aimed at limiting credit expansion. The passive policy stance in the CAMA contributed to a significant redistribution of the area's money stock.